Three Decades of Amyloid Beta Synthesis: Challenges and Advances - Kasim, Johanes K.; Kavianinia, Iman; Harris, Paul W. R.; Brimble, Margaret A. (Frontiers in Chemistry, 2019)
Aggregation of the pathological amyloid beta (Aβ) isoform Aβ1-42 into senile plaques is a neuropathological hallmark of Alzheimer’s disease (AD). The biochemical significance of this phenomenon therefore necessitates the need for ready access to Aβ1-42 for research purposes. Chemical synthesis of the peptide, however, is technically difficult to perform given its propensity to aggregate both on resin during solid phase peptide synthesis and in solution during characterisation. This review presents a chronological summary of key publications in the field of Aβ1-42 synthesis, dating back from its maiden synthesis by Burdick et al. Challenges associated with the preparation of Aβ1-42 were identified, and the solutions designed over the course of time critically discussed herein. Ultimately, the intention of this review is to provide readers with an insight into the progress that has been made in the last three decades, and how this has advanced broader research in AD.